Recognising depression in non-human primates: a narrative review of reported signs of depression - Jonas C. P. van Oosten; Annemie Ploeger; Elisabeth H. M. Sterck (PeerJ)
Major depressive disorder (depression) is a highly heterogenous human mental disorder that may have equivalents in non-human animals. Research into non-human depression teaches us about human depression and can contribute to enhance welfare of non-human animals. Here, we narratively review how signs of depression in non-human primates (NHPs) can be observed based on symptoms of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5). Furthermore, we propose diagnostic criteria of NHP depression and we review reports on signs of depression in NHPs. We diagnose an NHP with depression when it shows a core sign (depressed mood or anhedonia) alongside at least three other DSM-5-derived signs of depression. Results show that four out of six observable signs of depression are present in NHPs, occasionally lasting for months. However, only a group of six NHPs in one study met our proposed criteria for a diagnosis of depression. We call for more research into the co-occurrence of depressive symptoms in individual NHPs to establish the prevalence of depression in NHPs.